2021
DOI: 10.3389/fgene.2021.699550
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genomic Regions Influencing N-Metabolism and N-Excretion in Lactating Holstein- Friesians

Abstract: Excreted nitrogen (N) of dairy cows contribute to environmental eutrophication. The main N-excretory metabolite of dairy cows is urea, which is synthesized as a result of N-metabolization in the liver and is excreted via milk and urine. Genetic variation in milk urea (MU) has been postulated but the complex physiology behind the trait as well as the tremendous diversity of processes regulating the N-metabolism impede the consistent determination of causal regions in the bovine genome. In order to map the genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…It has been reported that DKK1 functioned as a prognostic or diagnostic marker for OS assessment, and DKK1 immunodepletion may also be used as an additional treatment for OS ( 48 ). TMCC2 acts as a member of transmembrane and coiled-coil domain family, and its-encoding proteins might locate in endoplasmic reticulum and invovled in amyloid precursor protein metabolic process and bone marrow hematopoiesis ( 49 , 50 ). In addition, TMCC2 is identified as a potential biomarker of steroid-induced osteonecrosis of the femoral head ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that DKK1 functioned as a prognostic or diagnostic marker for OS assessment, and DKK1 immunodepletion may also be used as an additional treatment for OS ( 48 ). TMCC2 acts as a member of transmembrane and coiled-coil domain family, and its-encoding proteins might locate in endoplasmic reticulum and invovled in amyloid precursor protein metabolic process and bone marrow hematopoiesis ( 49 , 50 ). In addition, TMCC2 is identified as a potential biomarker of steroid-induced osteonecrosis of the femoral head ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SFI1 gene, or centrin-binding protein also on OAR17, has been associated with reproductive traits [ 96 ], metabolic digestion [ 97 ], and interestingly, cold adaptation, as it affects basal metabolic rate [ 98 ]. In addition, in humans, this gene was proved to be associated with glycosylated haemoglobin [ 99 ], a marker of average blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, neither the cow individual N-uptake nor the content of N in urine and feces is measurable in practice operating dairy farms. Thus, in the last years the cow-specific MU concentration has been considered as a substitute trait (Burgos et al, 2007 , 2010 ; König et al, 2008 ; Honerlagen et al, 2021 ; Jahnel et al, 2021 ). MU values are available to breeding companies at a large scale due to the results of monthly milk records.…”
Section: Introductionmentioning
confidence: 99%